Examining the Determinants of Capital Structure of Blue-Chip Non-Financial Companies on the IDX - Khoirul Umam Hasbiy; Seri Suriani; I Wayan Ruspendi Junaedi; Puspa Rini; Melati Sukma Dewi Labusang (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
This study aims to examine the effect of the variables Financial Deficit, Diversification, Institutional Ownership, and Asset Structure on Capital Structure in Non-Financial Blue Chip companies listed on the Indonesia Stock Exchange in 2020-2022. The population in this study is 125 manufacturing companies listed on the Indonesia Stock Exchange in 2020 – 2022. The sampling technique used was purposive sampling and a sample of 52 companies was obtained. The data analysis technique used is multiple linear regression analysis. The results of this study indicate: (1) the financial deficit has no effect on capital structure, as evidenced by the test results of the calculated t value of 1.091 and a significance level of 0.277 so that H1 is rejected; (2) Diversification has a significant positive effect on Capital Structure as evidenced by the t-value of 3.081 with a significance level of 0.002 so that H2 is accepted; (3) Institutional Ownership has a significant negative effect on Capital Structure as evidenced by the t-value of -3.542 with a significance level of 0.001 so that H3 is accepted; (4) Asset Structure has a significant positive effect on Capital Structure as evidenced by the t value of 3.660 with a significance level of 0.000 so that H4 is accepted. Adjusted R Square value of 0.156 indicates that Capital Structure is influenced by Financial Deficits, Diversification, Institutional Ownership, and Asset Structure of 15.6% while the remaining 84.6% is influenced by other factors not examined in this study. Keywords: Assets, Capital, Financial, Diversification